THE EFFECT OF SALIVARY TESTOSTERONE LEVELS ON HEART RATE VARIBILITY ON STUDENTS OF MEDICAL FACULTY OF JENDRAL SOEDIRMAN UNIVERSITY - Widad Nurul Nadiyah; Mustofa Mustofa; Wahyu Djatmiko; Rizak Tiara Yusan (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Testosterone is a steroid hormone produced by Leydig cells in testis. Testosterone levels can be measured through a saliva sampel. Testosterone have effect in the cardiovascular system. Testosterone can affect cardiac contractility and has a cardioprotective role in maintaining the autonomic balance of the heart. Cardiac autonomic activity can be assessed by Heart Rate Varibility (HRV). This study aims to determine the effect of salivary testosterone levels on HRV in FK Unsoed students. This study was an analytic observational study with a cross sectional approach. The number of subjects in this study were 31 students who were taken by consecutive sampling, with inclusion criteria, namely male gender, age 17-25 years, agreed to the informed consent, BMI 18,5-24,9 kg/m2, body temperature 36,5-37,5 ℃, and low to moderate level of physical activity. Testosterone levels were measured using the Salimetrics ELISA method. HRV were measured using a POLAR M400 heart rate monitor and the Welltory application with the result of HRV parameters in the form of SDNN. The data normality test used the Saphiro-Wilk test. Bivariate analysis used Pearson’s correlative parametric test. The subjects of the study had a low mean testosterone saliva levels, namely 12,38±3,70 pg/mL and a low mean SDNN of 56,74±19,70 ms. The results of the Pearson correlation test of testosterone with SDNN shows the value of r = 0,147 and the value of p = 0,429, so it can be concluded that there is no correlation between testosterone saliva levels and HRV in SDNN parameters.